x3 - 4x2 + x + 6 The sum of the odd coefficients equals the sum of the even coefficients, so (x + 1) is a factor. So x3 - 4x2 + x + 6 = x3 + x2 - 5x2 - 5x + 6x + 6 = x2(x + 1) - 5x(x + 1) + 6(x + 1) = (x + 1)(x2 - 5x + 6) = (x + 1)(x - 2)(x - 3)
First factor is x, but we need to know the sign of 5x in your equation...
(x-2)(x+1)(x+5)
It is not possible to be sure about the answer because there is no sign before the linear term. If the polynomial is x3-4x2+x-4 then, the factors are (x-4) and (x2+1).
(x - 1)(x^2 - 5)
5x is a common factor of all terms:- 5x(x3+4x2+9)
Yes, if there is no remainder after division, the divisor is a factor.
X3 - 4X2 - 45XX(X2 - 4X - 45)=============X is only common factor here.
x3 + 4x2 + x + 4 = (x + 4)(x2 + 1)
x3 - 4x2 + x + 6 The sum of the odd coefficients equals the sum of the even coefficients, so (x + 1) is a factor. So x3 - 4x2 + x + 6 = x3 + x2 - 5x2 - 5x + 6x + 6 = x2(x + 1) - 5x(x + 1) + 6(x + 1) = (x + 1)(x2 - 5x + 6) = (x + 1)(x - 2)(x - 3)
x3 + 2x2 + 5x + 4 = (x + 1)(x2 + x + 4)
First factor is x, but we need to know the sign of 5x in your equation...
(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)
x3 + 12x2 - 5x = x(x2 + 12x - 5) = x(x + 6 - √41)(x + 6 + √41)
(x - 2)(x + 4)(x - 6)
if f(x) = x3 + 4x2 - 11x - 30, then yes, (x - 3) is indeed a factor. f(x) = x3 + 4x2 - 11x - 30 ∴ f(x) = (x - 3)(x2 + 7x + 10) ∴ f(x) = (x - 3)(x + 2)(x + 5)
(x + 1)(x - 2)(x + 5)